Students' Perceptions of Practicum Learning Media Used During the Covid-19 Pandemic - Sutirman; Riana Isti Muslikhah (Journal of Education Technology, 2023)
The problem behind this research is that there are practical lectures in tertiary institutions which cannot be carried out in person due to the Covid-19 pandemic. As a result, practical learning is carried out online. This study aims to analyze student perceptions of practical learning media carried out online during the Covid-19 pandemic and the obstacles faced by students in participating in online practical learning during the Covid-19 pandemic. This study uses a descriptive method with a quantitative approach. Research data was collected using a survey via an online questionnaire using the Google form. The research respondents consisted of 314 students. Research data were analyzed using descriptive analysis techniques. The research findings show that students have a good perception of the use of practical learning media conducted online during the Covid-19 pandemic. The media most often used and liked by students is Zoom. The main obstacle felt by students during online learning is an unstable internet network, so students cannot take part in practical learning to the fullest. The novelty in this study is to find out students' perceptions of using online practicum media that have not been carried out by previous researchers. The implication of this research is that online learning media can be used as an alternative to practicum learning media during the Covid-19 pandemic.